Assessment on risk management of helicopter services for offshore installations - Omar, Sabri; Johari, Muhd Khudri; Samad, Abdul Ghani Abdul (International Journal of Engineering and Technology, 2018)
The lack of research on risk assessment and awareness among authorized personnel handling helicopters at Malaysian offshore installations has been addressed in a recently-submitted review. The Air Accident Investigation Bureau (AAIB) and Civil Aviation Authority (CAA) has strongly recommended all helicopter companies to improve significantly on their helicopter maintenance, particularly for the ones involving offshore operations. From the perspectives of trainers in an approved training organization such as Universiti Kuala Lumpur - Malaysian Institute of Aviation Technology (UniKL MIAT), this issue has been raised among both training staffs and students. As a benchmark for everyone involved, a comprehensive questionnaire on both risk assessment and risk awareness has been developed and distributed to 15 highly-experienced helicopter handlers from five different respectable offshore installations. The analyzed results have determined that there is a significant correlation between the knowledge of risk assessment and perception on risk awareness among helicopter maintenance personnel on offshore installations.